O modifikovanim obogaćenim verzijama Browder-Göhde- Kirk teoreme nepokretne tačke - Chamoli, Divyanshu; Rawat, Shivam; Bisht, Monika; Dimri, R.C. (Vojnotehnički glasnik / Military Technical Courier, 2025)
In this paper, we propose a modified enriched version of the classical Browder-Göhde-Kirk fixed point theorem in the setting of uniformly convex Banach spaces. Furthermore, we define modified enriched asymptotically nonexpansive mappings and proved some results extending the Goebel-Kirk fixed point theorem for these types of mappings. These findings contribute to the ongoing development of fixed point theory and its applications in nonlinear analysis.